The Role of Local Government in Tourism Development of the Tanjung Lesung SEZ, Banten Province - Ardiatno Yanuadi; Lilis Sri Mulyawati; Novida Waskitaningsih; Denaya Putri Tien Sutini (Jurnal Planologi, 2026)
The Tanjung Lesung Special Economic Zone (SEZ) in Banten Province is one of Indonesia’s national priority destinations, and it is expected to drive regional economic growth through tourism. However, the declining trend in tourist arrivals indicates that its development impact has not been optimal. Specific studies on the government’s role within SEZs remain limited, especially regarding the Tanjung Lesung SEZ. This research fills that gap and offers applicable policy recommendations for tourism development. This article provides novelty by comprehensively examining the role of local government in tourism development within a Special Economic Zone, a topic not previously explored in depth. It also integrates policy aspects, government roles, and the challenges faced in a post-disaster and pandemic context. A qualitative descriptive approach was employed, with primary data collected through interviews and FGDs involving key stakeholders, and secondary data from official documents and statistical records. Data were analyzed using thematic content analysis, with triangulation and coding guided by Veal’s (2017) Tourism Policy Framework. The findings indicate that the local government performs crucial roles as a regulator, facilitator, coordinator, motivator, and dynamizer. However, effectiveness is hindered by shifts in national regulations, fragmented coordination, infrastructure development delays, inadequate destination branding, and limited community engagement. These results highlight the need to strengthen coordination, clarify institutional authority, and enhance local community capacity to support sustainable tourism development in SEZs. Furthermore, the study explicitly applies tourism governance theory to contextualize the findings, underscoring the importance of multi-level coordination and stakeholder collaboration in effective SEZ management. Keywords: Tanjung Lesung SEZ, Local Government Roles, Tourism Development, Regulatory Challenges Kawasan Ekonomi Khusus (KEK) Tanjung Lesung di Provinsi Banten merupakan salah satu destinasi prioritas nasional yang diharapkan mendorong pertumbuhan ekonomi regional melalui sektor pariwisata. Namun, penurunan tren kunjungan wisatawan menunjukkan bahwa dampak pengembangannya belum optimal. Studi spesifik mengenai peran pemerintah dalam pengembangan KEK masih sangat terbatas, khususnya terkait KEK Tanjung Lesung. Oleh karena itu, penelitian ini penting untuk mengisi kekosongan tersebut dan menawarkan rekomendasi kebijakan yang aplikatif bagi pengembangan pariwisata. Artikel ini memberikan kebaruan dengan mengkaji secara komprehensif peran pemerintah daerah dalam pengembangan pariwisata di kawasan KEK, sebuah topik yang sebelumnya belum pernah dieksplorasi secara mendalam. Penelitian ini juga mengintegrasikan aspek kebijakan, peran pemerintah, dan tantangan yang dihadapi dalam konteks pasca-bencana dan pandemi. Pendekatan deskriptif kualitatif digunakan, dengan data primer diperoleh melalui wawancara dan FGD bersama pemangku kepentingan utama, serta data sekunder dari dokumen resmi dan data statistik. Analisis dilakukan menggunakan thematic content analysis dengan triangulasi data dan pengkodean berdasarkan kerangka Veal (2017). Hasil penelitian menunjukkan bahwa pemerintah daerah berperan sebagai regulator, fasilitator, koordinator, motivator, dan dinamisator, namun efektivitasnya masih terkendala oleh perubahan regulasi pusat, lemahnya koordinasi, keterlambatan pembangunan infrastruktur, rendahnya branding destinasi, dan partisipasi masyarakat yang terbatas. Temuan ini menekankan pentingnya penguatan koordinasi, kejelasan kewenangan kelembagaan, dan peningkatan kapasitas masyarakat lokal untuk mendukung pengembangan pariwisata berkelanjutan di KEK. Selain itu, penelitian ini secara eksplisit menerapkan teori tata kelola pariwisata untuk mengontekstualisasikan temuan, menekankan pentingnya koordinasi multi-level dan kolaborasi pemangku kepentingan dalam pengelolaan KEK yang efektif.Kata Kunci: KEK Tanjung Lesung, Peran Pemerintah Daerah, Pengembangan Pariwisata, Tantangan Regulasi